Endocrine-active and endocrine-disrupting compounds in food – occurrence, formation and relevance - Stiefel, Constanze; Stintzing, Florian (NFS journal, 2023)
Over the last decades, global concerns regarding possible adverse health effects of chemical pollutants on the hormonal systems of living organisms in wildlife and humans are constantly growing. Endocrine-active and endocrine-disrupting chemicals (EDC) belong to a heterogeneous class of exogenous chemicals, including various persistent anthropogenic contaminants, pesticides, distinct substances used in consumer products, and also natural compounds. Exposure through the food chain is considered essential for most EDC, while they may enter the food chain as residues from animal- or plant-based food production (e.g. pesticides or pharmaceutical residues), may be released from food contact materials, may be present due to natural contamination (e.g. mycoestrogens), may enter via a polluted environment and also as natural plant food ingredients (e.g. phytoestrogens). The complexity of the subject is due to: a) the ubiquitous occurrence and hardly possible avoidance of many substances with supposed endocrine properties, b) the scientific disagreement among experts and the huge number of partly controversial study outcomes and c) the increasing pressure of the public, necessitating a higher level of transparency and clear-cut orientation with respect to avoidance and reduction strategies. In this light, the current review intends to provide an overview of the historical and regulatory developments regarding the topic of EDC, discusses the important difference between endocrine-active and disruptive substances and presents some key characteristics of endocrine acting substances for a better understanding of their relevance for the food chain including possible long-term effects, windows of sensitivity, low-dose and possible “cocktail” effects. In addition, a comprehensive overview on the different exposure paths of endocrine-active and disruptive substances in the food chain is given, with both a focus on naturally occurring food ingredients and possible contaminations from external sources.